2004
DOI: 10.1021/cm035129x
|View full text |Cite
|
Sign up to set email alerts
|

Fractal Dimension and Cobalt Leaching in CoX and CoA Zeolites

Abstract: Cobalt-exchanged A and X zeolites are studied by infrared spectroscopy and small-angle X-ray scattering. Samples were irradiated and heated until the zeolite structure collapsed. We found that cobalt leaching depends on the fractal dimension regardless of the nature of the zeolite and the irradiation treatment. Heating and γ-irradiation destroys the zeolite network as found by infrared spectroscopy. The modifications in the 4R and 6R pore opening vibrations show that the cobalt sites are altered by thermal and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2005
2005
2011
2011

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 20 publications
1
11
0
Order By: Relevance
“…The results on thermally treated Co 2+ and Cs + exchanged zeolites reproduce those reported in previous studies [3,[17][18][19]. In thermal treatment, as temperature increases, cobalt migrates from large cavities to sodalite cages which provide high coordination sites [20][21][22].…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…The results on thermally treated Co 2+ and Cs + exchanged zeolites reproduce those reported in previous studies [3,[17][18][19]. In thermal treatment, as temperature increases, cobalt migrates from large cavities to sodalite cages which provide high coordination sites [20][21][22].…”
Section: Discussionsupporting
confidence: 86%
“…Studying the cobalt environment in irradiated exchanged zeolites A and X, we found that leaching depended on the fractal dimension regardless of the nature of the zeolite [17]. In this sense, it is interesting to note that ion-exchange, followed by calcination, creates a porous surface on the zeolite crystals which initially restricts cation loss [23].…”
Section: Discussionmentioning
confidence: 99%
“…In our case, zeolites are objects which are surfaces that, of course, exist in a three dimensional world. Fractal dimension is a valuable parameter to understand the degree of imperfections in the zeolite lattice [32]. Note that, the presence of extra-framework species in cavities reduces the connectivity of the lattice, i.e.…”
Section: Resultsmentioning
confidence: 99%
“…Zeolites A samples were heated at 673 and 1073 K and the X samples at 673 and 973 K for 12 h. In previous works [7,14] we found that sodium or cobalt A zeolites treated at 1073 K recrystallized as nepheline and carnegeite. Instead, sodium and cobalt X zeolites are stable at temperatures of 973 K. We chose these temperatures to study, first, the behavior of a recrystallized zeolite, zeolite A.…”
Section: Thermal Treatmentmentioning
confidence: 92%